2018
DOI: 10.1007/s10517-018-4013-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous Melatonin in the Regulation of Th17/Treg Balance during Pregnancy

Abstract: We studied the role of endogenous melatonin in the development and functioning of T cells that produce IL-17 (Th17) and regulatory T cells (Treg) during pregnancy. The study was performed ex vivo and in vitro with auto-serum as the source of endogenous melatonin under conditions of blockade of melatonin-dependent signaling. Participation of the hormone in the regulation of differentiation of both CD4RORγt and CD4FoxP3T cells and their key products IL-17A and TGF-β was demonstrated. It is known that the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…In the present study, it was observed that the expression of FoxP3 and IL-35 declined in patients with GDM and DPE, suggesting that a reduced production of Treg cells may lead to inflammation. IL-17 and CRP are involved in low-grade inflammation (55). IL-17 is a characteristic inflammatory cytokine expressed by Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was observed that the expression of FoxP3 and IL-35 declined in patients with GDM and DPE, suggesting that a reduced production of Treg cells may lead to inflammation. IL-17 and CRP are involved in low-grade inflammation (55). IL-17 is a characteristic inflammatory cytokine expressed by Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin treatment can reduce lipid peroxidation induced by obstructive cholestasis during the last third of pregnancy in rats by stimulating the expression of components of the endogenous cellular antioxidant defence in the maternal liver 66 . The melatonin levels in hepatocytes are independent of pineal‐derived melatonin, which provides hepatocytes with a buffer against free radicals 29 . Hepatocytes play a role as ‘accessory’ cells in both the afferent and efferent arms of the cell‐mediated immune response 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin treatment can increase pregnenolone synthesis in the ovary and endometrium, which promotes endometrial development and embryo implantation early in mouse pregnancy 28 . T‐cell subpopulations, IL‐17 (Th17) and regulatory T (Treg) cells, have an essential role during pregnancy, and endogenous melatonin is involved in regulating the Th17/Treg balance during pregnancy in humans 29 . It has been reported that the characteristics of the melatonin secretory rhythm are unaffected by steroids during the oestrous cycle and pregnancy in Ile‐de‐France ewes 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Both physiological and pharmacological levels of melatonin induce in vitro differentiation of intact CD4 + T cells in Th17 [108]. Recently, ex vivo and in vitro studies using auto-serum as a source of endogenous melatonin, showed differentiation in both CD4 + RORγt + and CD4 + FoxP3 + T cells, leading to an inverse balance of Th17/Treg [109]. Although melatonin's functions on the maternal-fetal immune cells are not completely defined, exogenous melatonin is documented to have beneficial effects for mother and fetus in the context of immunocompromised pregnancy.…”
Section: Melatonin's Action On the Immune Microenvironment At The Matmentioning
confidence: 99%